Pakistan, Ministry of Finance, Revenue and Economic Affairs. Report of Prime Minister's Task Force on Agriculture. Islamabad. December 1993. 68 pp. (The Pakistan Development Review, 1994)
In consonance with her commitment to the enhanced welfare of the masses, the Prime Minister of Pakistan, shortly after assuming the office, set up a "Task Force on Agriculture" to look into the problems of agriculture in general and issues of agricultural taxation including Ushr in particular and to submit a report in six weeks. The task force worked day and night to comply with the Prime Minister's directive and submitted its report within the stipulated time. As must be clear from the terms of reference, the task force was to define the major problems of agriculture and to recommend solutions that are practical and acceptable to all concerned. Before going into the specific problems and justifiable recommendations, the report presents an overview of the state of the art in agriculture and pinpoints the facts that agriculture is still the major sector of the Pakistani economy in many ways, and that its growth performance, though laudable, has progressively fallen in the Eighties with signs of stagnating agricultural production in the Nineties. These trends, coupled with the rapid growth of population, have resulted in mounting import bills of basic foods against scarce foreign exchange earnings.